Evaluation of the Performance of Vortex Generators on the DU 91-W2-250 Profile using Stereoscopic PIV - Clara Marika Velte (Journal of Systemics, Cybernetics and Informatics, 2009)

(untitled)
Stereoscopic PIV measurements investigating the effect of Vortex Generators on the lift force near stall and on glide ratio at best aerodynamic performance have been carried out in the LM Glasfiber wind tunnel on a DU 91-W2-250 profile. Measurements at two Reynolds numbers were analyzed; Re=0.9·10 6 and 2.4·10 6 . The results show that one can resolve the longitudinal vortex structures generated by the devices and that mixing is created close to the wall, transferring high momentum fluid into the near wall region. It is also seen that the vortex generators successfully can obstruct separation near stall.